Design of a defense hole system for a uniaxially loaded plate - Choy, Wei Han (2015)
Minimizing stress concentration due to geometric discontinuities in structures is important to ensure longer fatigue life and avoid catastrophic failures, which may incur injuries and financial losses. It is also important to know which regions have the highest likelihood of crack initiation so that precautionary measures can be taken. A comprehensive plane stress boundary element method study is made of the effect of introducing an oblong defense hole system on the stress concentration factor (SCF) about a circular main hole in a rectangular uniaxially loaded plate. Meshes of the plate models using elements and nodes were created and processed using the BIE2DS boundary element method program. The study investigated the optimal location and size of the oblong auxiliary holes, as well as the effect of varying the ‘oblongity’ of the auxiliary holes on the SCF at the main hole. The results show that the closer the auxiliary holes to the main hole, the greater the reduction of SCF at the main hole. Also, the SCF at the main hole could be further reduced by auxiliary holes of larger diameters. A maximum reduction in main hole SCF of 18.77% was achieved. The results also indicate that when the oblong auxiliary holes are stretched along the direction of loading, the SCF at the main and auxiliary holes increased. When the auxiliary holes are stretched in the direction perpendicular to loading, the SCF at the main hole drops, but increases at the auxiliary holes. Introducing the defense hole system was also found to reduce the stress intensity factor of cracks emanating from the main hole up to a certain crack length. Thus, this method can be used to improve the fatigue life of a component.